(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
This topic is one of the sensitive and important topics because the scholars are the tool of notable and discipline, and with their righteousness and wisdom is the good of the nation as rulers and the ruled, so this research was to clarify the rights and duties and the optimal role of the scholars in authority. As this research included looking at the relationship of scholars with authority, through the support of the authority in Andalusia for scholars by honoring them, increasing donations, praying for them, bringing them closer and encouraging them, in order to show their best for the development of the scientific movement in Andalusia, as well as benefiting from them within the court of power. The research dealt with the names of all the Umayyad princes and caliphs in Andalusia from the year (138-399 AH / 755-1008 CE), and each prince or caliph had a specific perspective on how to deal with scholars, as the political position had an important role in determining this relationship according to the stability of the situation in Andalusia, and by that we mean that some of the princes and caliphs were distinguished by their reign of calm and stability, which made the authority direct all its energies to increase interest in scholars and get closer to them, in order to develop the movement of the scientific movement in Andalusia, and on the other hand, the reign of some princes and caliphs was characterized by turbulence and political instability due to strife and internal and external problems Of course, it affected the situation in Andalusia, neglecting the scientific movement and not caring for scientists. In conclusion, this research came with importance, objectives, and a preliminary, and it consisted of one topic, which is the historical perspective of the relationship of scholars with princes and caliphs from the year (138-399 AH / 755-1008 AD), as well as a conclusion and results, and a list of sources and references